Divergent in shape and convergent in function: Adaptive evolution of the mandible in Sub‐Antarctic mice. (1st April 2018) - Renaud, Sabrina; Ledevin, Ronan; Pisanu, Benoit; Chapuis, Jean‐Louis; Quillfeldt, Petra; Hardouin, Emilie A.
Abstract: Convergent evolution in similar environments constitutes strong evidence of adaptive evolution. Transported with people around the world, house mice colonized even remote areas, such as Sub‐Antarctic islands. There, they returned to a feral way of life, shifting towards a diet enriched in terrestrial macroinvertebrates. Here, we test the hypothesis that this triggered convergent evolution of the mandible, a morphological character involved in food consumption. Mandible shape from four Sub‐Antarctic islands was compared to phylogeny, tracing the history of colonization, and climatic conditions. Mandible shape was primarily influenced by phylogenetic history, thus discarding the hypothesis of convergent evolution. The biomechanical properties of the jaw were then investigated. Incisor in‐lever and temporalis out‐lever suggested an increase in the velocity of incisor biting, in agreement with observations on various carnivorous and insectivorous rodents. The mechanical advantage related to incisor biting also revealed an increased functional performance in Sub‐Antarctic populations, and appears to be an adaptation to catch prey more efficiently. The amount of change involved was larger than expected for a plastic response, suggesting microevolutionary processes were evolved. This study thus denotes some degree of adaptive convergent evolution related to changes in habitat‐related changes in dietary items in Sub‐Antarctic mice, but only regarding simple, functionally relevant aspects of mandible morphology.